2003
DOI: 10.1029/2002jd002321
|View full text |Cite
|
Sign up to set email alerts
|

Variability of biomass burning aerosol optical characteristics in southern Africa during the SAFARI 2000 dry season campaign and a comparison of single scattering albedo estimates from radiometric measurements

Abstract: [1] Measurements of the column-integrated aerosol optical properties in the southern African region were made by Aerosol Robotic Network (AERONET) Sun-sky radiometers at several sites in August-September 2000 as a part of the Southern African Regional Science Initiative (SAFARI) 2000 dry season field campaign. Fine mode biomass burning aerosols dominated in the northern part of the study region (Zambia), which is an active burning region, and other aerosols including fossil fuel burning, industrial, and aeolia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
298
4
10

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(338 citation statements)
references
References 50 publications
26
298
4
10
Order By: Relevance
“…This compares with values of 0.85-0.90 measured during the Southern African Regional Science Initiative (SAFARI-2000) (Eck et al, 2003;Haywood et al, 2003a;Leahy et al, 2007). In contrast, the dust aerosol was very weakly absorbing with single-scattering albedos of around 0.98 at 550 nm .…”
Section: Introductionsupporting
confidence: 63%
“…This compares with values of 0.85-0.90 measured during the Southern African Regional Science Initiative (SAFARI-2000) (Eck et al, 2003;Haywood et al, 2003a;Leahy et al, 2007). In contrast, the dust aerosol was very weakly absorbing with single-scattering albedos of around 0.98 at 550 nm .…”
Section: Introductionsupporting
confidence: 63%
“…Example of this circulation is visible in Fig. 1, which represents the statistical distribution of HYSPLIT 96-h back trajectories (Draxler and Hess, 2004) for the observational period of this paper.…”
Section: Meteorologymentioning
confidence: 95%
“…especially optical properties of submicron aerosol particles have mainly been investigated during the SAFARI 1992 and SAFARI 2000 measurement campaigns Ross et al, 2003;Eck et al, 2003). On a long-term basis, the South African Weather Service and NOAA-ESRL have conducted observations of aerosol number concentrations and optical properties such as light scattering and absorption as part of the Global Atmosphere Watch (GAW) program at the station in Cape Point (e.g.…”
Section: Laakso Et Al: South African Eucaari Measurementsmentioning
confidence: 99%
“…Previous studies have indicated that South Africa is one of the countries in the world that is largely affected by aerosol load, due to various natural and anthropogenic sources (Piketh et al, 2000Formenti et al, 2002Formenti et al, , 2003Campbell et al, 2003;Eck et al, 2003;Freiman and Piketh, 2003;Ichoku et al, 2003;Ross et al, 2003;Winkler et al, 2008;Queface et al, 2011;Tesfaye et al, 2011;Venter et al, 2012;Tiitta et al, 2014). Intensive efforts have been undertaken during recent years to characterize aerosol pollution in South Africa.…”
mentioning
confidence: 99%